Formulación de un Plan de capacitación dirigido a los servidores públicos del GAD - Municipal del cantón Loja, año 2023 - Rueda Rueda, Cristina Vanelli (2024)
The present Curricular Integration Work entitled "Formulation of a Training Plan aimed for public workers of the GAD - Municipal of the Loja canton, year 2023" was carried out by reviewing whether the institution has any training mechanism for its officials and verifying the needs of public servants. As a result, a training plan was proposed with the aim of providing staff members with a training schedule that will allow them to keep updated on topics related to their field of work. This in turn, enables them to perform their duties in a suitable environment and achieve better results. The methods applied include analytical and synthetic approaches, with a qualitative and quantitative focus. Research techniques such as exploratory-descriptive scope, interview, survey, bibliographic and documentary review, helped indentifying results such as knowing the training needs of public workers and thus being able to implement a training plan adapting to these needs, allowing to improve the knowledge and skills of the officials and therefore the outcomes of their functions; in the same way to provide a better service to users of the Loja city.